2016
DOI: 10.1007/s11629-015-3465-2
|View full text |Cite
|
Sign up to set email alerts
|

Driving force and changing trends of vegetation phenology in the Loess Plateau of China from 2000 to 2010

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…These results indicate that the climate in the study area is becoming warmer and drier, which leads to drought, as Li et al and Zhao et al reported [76,77]. In a water-limited area, the spatial distribution of precipitation determines the vegetation distribution and growth [9]. Zhang et al pointed out that, compared with other areas that suffered drought, precipitation in the northern part of the Jinghe River basin is relatively sufficient, which is likely to be the reason that vegetation restoration dominated by climate factors is concentrated in that area [78].…”
Section: Driving Forcessupporting
confidence: 60%
See 1 more Smart Citation
“…These results indicate that the climate in the study area is becoming warmer and drier, which leads to drought, as Li et al and Zhao et al reported [76,77]. In a water-limited area, the spatial distribution of precipitation determines the vegetation distribution and growth [9]. Zhang et al pointed out that, compared with other areas that suffered drought, precipitation in the northern part of the Jinghe River basin is relatively sufficient, which is likely to be the reason that vegetation restoration dominated by climate factors is concentrated in that area [78].…”
Section: Driving Forcessupporting
confidence: 60%
“…However, it is difficult to distinguish the influence of these two driving factors when both function in the process of vegetation growth [7]. Particularly in arid and semi-arid regions such as the Loess Plateau, the water-limited environment makes the vegetation there highly sensitive to changes in temperature and precipitation [8,9], and high-intensity human activities easily may lead to degradation of the local vegetation [10][11][12][13]. To improve the ecological environment, the local government has implemented a series of ecological restoration programs, such as the Grain for Green region [46].…”
Section: Introductionmentioning
confidence: 99%
“…The timing and length of growing season are important for agricultural production, ecological security, and human activities [3,13,19]. Both observations and model simulations show a decrease in the number of frost days and an increase in the length of the growing season in the second half of the twentieth century [1].…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased temperature and precipitation have extended the growing season of the vegetation in the Loess Plateau. However, if the rainfall fails to offset the increased evapotranspiration caused by the warming climate, the length of the growing season will be shortened [22]. On the other hand, human activity also affects vegetation growth [23][24][25].…”
Section: Introductionmentioning
confidence: 99%